An experimental study and failure mechanism analysis on dynamic behaviors of plain concrete under biaxial compression-compression. (December 2022) - Yu, Zhenpeng; Shen, Linsong; Tang, Rui; Huang, Qiao
Abstract: In order to explore the dynamic mechanical properties of concrete under biaxial compression-compression, a true triaxial instrument was used to conduct an experimental study on the dynamic mechanical properties of plain concrete under biaxial compression-compression. Eight different lateral compressive stresses (0 MPa~14 MPa) and four strain (10 −5 /s, 10 −4 /s, 10 −3 /s and 10 −2 /s) rate were considered. From this, the effects of lateral compressive stress and loading strain rate on the biaxial compression-compression properties of concrete were compared and analyzed by obtaining the failure modes, principal compressive stress-strain curves and related mechanical characteristic parameters of plain concrete under different loading conditions. The research results show that: with the increase of lateral compressive stress, the failure modes of concrete were developed from columnar failure at low lateral compressive stress to sheet-like failure at high lateral compressive stress. With the increase of lateral stress, the development trend of concrete failure mode decreased gradually under the influence of strain rate. With the increase of lateral compressive stress, the variation range of concrete principal compressive stress decreased first and then tended to be relatively stable under the influence of strain rate. With the increase of strain rate, the increase range of concrete principal compressive stress decreased under the influence of lateral compressive stress. The influence mechanism of lateral compressive stress and strain rate on biaxial compression-compression performance of concrete was analyzed. Meanwhile, based on Kupfer biaxial compression failure criterion, a biaxial compression dynamic failure criterion model considering the effect of loading strain rate on plain concrete was proposed. The research results provided an important theoretical basis for the application and development of concrete engineering.